"KelPUS-Gendang Beleq" Model as A Strategy to Improve Knowledge and Attitudes of Couples of Childbearing Age against Long Term Contraception Method - Awan Dramawan; Moh. Arip; Desty Emilyani (Health Notions, 2018)
The "KelPUS-GENDANG BELEQ" model design is an intervention given to couples of childbearing age, by making a model of the couples of child-bearing age combined with traditional "Gendang Beleq" art, as a media for counseling and a strategy for improving knowledge and attitude of the couples of child-bearing age against Long Term Contraception Methods. The aim of this research was to know the characteristic of couples of childbearing age, to increase knowledge and attitude of couples of childbearing age to long term contraception method through model design of "Kelpus-Gendang Beleq" in Darek Village, Praya Barat Daya Subdistrict, Lombok tengah Regency, NTB Province. Subjects were couples of child-bearing age who were registered as family planning acceptors in January 2015 to May 2016 in Darek Village, Praya Barat Daya Sub-district, Lombok Tengah. The sample size was 60 couples of childbearing age, consisting of: 30 people as control group and 30 people as intervention group. After the data collected, data analysis was done using Wilcoxon Signed rank test and Mann Whitney-U test. The result of the research shows that traditional music art of Sasak tribe "KelPUS Gendang Beleq" proved effective to increase knowledge and attitude of fertile couples about the use of long term contraception method. Key words: Gendang Beleq, Counseling, Long-term contraception method